2014
DOI: 10.1111/jam.12681
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous remediation of nutrients from liquid anaerobic digestate and municipal wastewater by the microalga Scenedesmus sp. AMDD grown in continuous chemostats

Abstract: The study is the first to report stable, long-term continuous algal growth and productivity obtained by combining wastewaters of different sources. The study is supported by detailed analyses of the composition of the cultivated biomass and links composition to the nutrient and light availabilities in the cultures. Simultaneous remediation of these wastes by algal growth is discussed as a strategy for the valorization of the biomass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Glucose was added as an easily assimilable substrate at 1 gl -1 (by weight) in the control condition because this concentration can be used to assess whether a microalgae growth inhibition correlated to microalgae capacity to use glucose in their mixotrophic and heterotrophic metabolic condition (Pentose Phosphate Pathway and Embden-Meyerhof Pathway respectively) exists (Yeh et al, 2012). Specific growth rate (μ, d -1 ) was calculated for every experimental condition as reported by Dickinson (2014), by the equation 1:…”
Section: Anaerobic Digestate Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose was added as an easily assimilable substrate at 1 gl -1 (by weight) in the control condition because this concentration can be used to assess whether a microalgae growth inhibition correlated to microalgae capacity to use glucose in their mixotrophic and heterotrophic metabolic condition (Pentose Phosphate Pathway and Embden-Meyerhof Pathway respectively) exists (Yeh et al, 2012). Specific growth rate (μ, d -1 ) was calculated for every experimental condition as reported by Dickinson (2014), by the equation 1:…”
Section: Anaerobic Digestate Characterizationmentioning
confidence: 99%
“…The scientific literature reports few papers about microalgae cultivation on OFMSW digestate or codigestion OFMSW and sludge (Massa et al, 2017;Zuliani et al, 2016a) and on municipal sludge digestate (Cai et al, 2013c(Cai et al, , 2013aCho et al, 2013Cho et al, , 2011Dickinson et al, 2014;Uggetti et al, 2014;Veronesi et al, 2015b;Yun et al, 2015). Most of these digestate sludges were pretreated to allow sterilization (autoclavation or ultrafiltration) and used with dilution.…”
Section: Introductionmentioning
confidence: 99%
“…Like most microalgae species in the Scenedesmus genus, S-AMDD is non-motile and colonial; typically forming clumps of f our cells or sometimes eight or more under environmentally stressful conditions [27,28]. In recent years, S-AMDD has been the focus of several studies to assess its potential as a feedstock for biofuels and bioremediation [29][30][31][32][33][34][35][36] while the evaluation of its potential suitability as a novel animal feed ingredient has only just begun [37,38]. In an initial study; S-AMDD demonstrated rapid growth rate and biomass productivity during exponential growth phase and the resulting biomass appeared to have good potential for animal nutrition based on its attractive proximate composition, favorable essential amino acid, fatty acid and elemental profiles and lack of contaminating heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…MBWT can be considered as a biological treatment method, aiming to the reduction of both, inorganic (primarily N and P) and organic load of wastewater (Dickinson et al, 2015;Park et al, 2011). However, ammonia-rich wastewaters display a major limitation to be treated with MBWT, due to the occurrence of ammonia toxicity.…”
Section: Introductionmentioning
confidence: 99%